Tribological behaviour of 3D printed materials for small joint implants: A pilot study. (August 2022) - Ranuša, Matúš; Čípek, Pavel; Vrbka, Martin; Paloušek, David; Křupka, Ivan; Hartl, Martin
Abstract: Additive manufacturing is a progressive method in endoprosthetics enabling customisation of implants. However, the challenge is to design articulating surfaces that are wear resistant in a long term. To tackle this challenge, it is necessary to understand the interaction between the surfaces and the lubricant synovial fluid as well as the mechanism of lubrication film formation. In this study we observed three synovial fluid constituents (albumin, γ-globulin a hyaluronic acid) in the contact area simultaneously with the coefficient of friction (CoF). Two metal alloys, CoCrMo and Ti6Al4V covered by DLC, were selected for the experiments as they are both suitable for the additive technology and commonly used in implants manufacturing. The tests were running on a custom-made pin-on-plate tribometer equipped for optical fluorescence measurements. The test apparatus allowed reciprocating motion and observation of the contact area. Our results showed differences in the pace of the CoF increase between the alloys and differences between the samples manufactured by the conventional and the additive manufacturing method. Both the conventionally and additively manufactured CrCrMo samples showed a stable CoF values from the beginning of the experiments: 0.66 (SD 0.02) for the conventional manufacturing CrCrMo samples and 0.53 (SD 0.01) for the additive manufacturing CrCrMo samples. The Ti6Al4V/DLC samples showed a stable CoF values similar to those of the CoCrMo samples not until the 240 s of experiment. These results are related to the protein formation in the contact areas as suggested by a similar increasing trend of the individual synovial fluid constituents in the contact. Increasing protein amounts in the contact led to CoF increase. There were also differences in the ratios of the individual constituents, where both the CoCrMo and the Ti6Al4V/ DLC samples manufactured additionally showed lower concentrations of γ-globulin and hyaluronic acid. These pilot results, on the one hand, support the potential of the additive manufacturing in the implantology and, on the other hand, demonstrate the application of a method suitable for the analysis of the lubricant behaviour in the contact. The method is limited in using the intensity of the emitted light to observe the behaviour of the lubricant film. Future development of the method will require a direct quantification of film thickness. Graphical abstract: Image 1